Valorization of keratin waste biomass and its potential applications. (April 2021) - Chaitanya Reddy, Chilakamarry; Khilji, Irshad Ahamad; Gupta, Arun; Bhuyar, Prakash; Mahmood, Syed; Saeed AL-Japairai, Khater Ahmed; Chua, Gek Kee
Graphical abstract: Highlights: First review on valorization of keratin-based waste in water processing applications. Wool, feather and hair as source of keratinous material with high protein content. An inexpensive source of digestible protein and amino acids by degradation of keratin waste. Various established and upcoming techniques to valorize the keratin waste have been reviewed. Abstract: Keratin is a major structural protein with high sulphur content. It is predominantly found in chicken feathers, wool, hair, hoof, and nails. Over the years, the accumulation of keratin waste has become an uncontrollable entity throughout the world. Environmental aspects may reduce the load of waste generation by waste process engineering. Such studies focus on the safe and effective conversion of keratin-based slow degradable wastes by green methods. Different methods of waste-conversion, like chemical and thermal, have been discussed. Various keratin degradation methods have been investigated like hydrolysis under pressure by using steam, enzymatic and chemical hydrolysis. The significance of keratin with potential applications and aid in the advancement of several environmentally sound bioproducts are described, including various keratin utilisation methods with its applications. More advantageous are enzymatic and bioconversion methods which assure milder conditions and preserve nutritional properties of the produced biomass. Keratinous wastes can be used as feedstock; however, appropriate processing is required to valorise the waste. In the present scenario, the accumulation of waste is causing water pollution, environmental damage and threatening human lives is discussed. At the end of the article, various critical applications, including waste process engineering, are summarised. This review concludes with a study on the conversion of keratinous waste into consumable products to minimise pollution.